Combining therapeutic antibodies using basiliximab and etanercept for severe steroid-refractory acute graft-versus-host disease: A multi-center prospective study. (4th March 2017) - Tan, Yamin; Xiao, Haowen; Wu, Depei; Luo, Yi; Lan, Jianping; Liu, Qifa; Yu, Kang; Shi, Jimin; He, Jingsong; Zheng, Weiyan; Lai, Xiaoyu; Zhu, Yuanyuan; et al.
ABSTRACT: Acute graft versus host disease (aGVHD) remains a major problem after allogeneic hematopoietic stem cell transplantation. Standard frontline therapy for aGVHD involves corticosteroids. However, fewer than half of patients have a lasting complete response. The long-term mortality rate of steroid-refractory aGVHD (SR-aGVHD) remains around 70%. To date, no consensus has been reached regarding the optimal salvage treatment for SR-aGVHD. We performed the first prospective, multi-center clinical trial to assess the efficacy and safety of a novel approach to treat severe (grades III–IV) SR-aGVHD with the combination of basiliximab and etanercept. Sixty-five patients with severe SR-aGVHD from six centers were included. The median number of basiliximab infusions was 4 (range 2–11) and of etanercept was 9 (range 2–12). At day 28 after starting the combination treatment, overall response (complete and partial response: CR+PR) to second-line treatment was 90.8% with 75.4% being CR. The incidences of CR per organ were 100%, 73.8%, and 79.7% for skin, liver, and gut involvement, respectively. Patients >30-y old ( p = 0.043, RR = 3.169), development of grades III–IV liver aGVHD ( p = 0.007, RR = 5.034) and cytomegalovirus (CMV) reactivation ( p = 0.035, RR = 4.02) were independent predictors for incomplete response. Combined treatment with basiliximab and etanercept resulted in improved CR to visceral aGVHD and significantly superior 2-y overall survival (54.7% vs. 14.8%, p <0.001) compared with classical salvage treatments. Our data suggest that the combination of basiliximab and etanercept may constitute a promising new treatment option for SR-aGVHD.